Beginning build and release management with TFS 2017 and VSTS : leveraging continuous delivery for your business - Chandrasekara, Chaminda (Apress, 2017)
"Learn how to master build and release management with Team Foundation Service and Visual Studio Team Services to facilitate the continuous delivery of software updates to your development team. You receive detailed, practical guidance on automating deployments of web sites in Azure App Service, database deployments to Azure platform, Micro Services deployments in Azure Service Fabric, and more. Each deployment is structured with the aid of hands-on lessons in a given target environment designed to empower your teams to achieve successful DevOps, This book provides lessons on how to optimize build release management definitions using capabilities, such as task groups. With the help of practical scenarios, you'll also learn how to diagnose and fix issues in automated builds and deployments. You'll see how to enhance the capability of build and release management, using team services/TFS Marketplace extensions and writing your own extensions for any missing functionality via hands on lessons. What you will LearnAutomate deployment to Azure platform, including Web App Service, Azure SQL and Azure Service Fabric. Test automation integration with builds and deploymentsPerform Dynamic CRM deployments handling and package management with TFS/VSTSExamine requirement to production delivery traceability in practical terms Review cross platform build/deployment capabilities of TFS/VSTS"--